2004
DOI: 10.1097/01.ju.0000140257.05714.45
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Critique of the Literature Relating Hospital or Surgeon Volume to Health Outcomes for 3 Urological Cancer Procedures

Abstract: Outcomes after radical prostatectomy and cystectomy are on average likely to be better if these procedures are performed by and at high volume providers. For radical nephrectomy the evidence is unclear. The impact of volume based policies (increasing volume to improve outcomes) depends on the extent to which "practice makes perfect" explains the observed results. Further studies should explicitly address selective referral and confounding as alternative explanations. Longitudinal studies should be performed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
84
2
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 46 publications
3
84
2
3
Order By: Relevance
“…This is at odds with a systematic review which suggested that provider volume (both hospital and surgeon) is an acceptable surrogate measure for quality-of-care in uro-oncological procedures [10]. In explaining why the panel did not enforce volume indictors, it may reflect the heterogeneity of the group or the contradicting evidence of a volume: quality relationship across all fields of medicine.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…This is at odds with a systematic review which suggested that provider volume (both hospital and surgeon) is an acceptable surrogate measure for quality-of-care in uro-oncological procedures [10]. In explaining why the panel did not enforce volume indictors, it may reflect the heterogeneity of the group or the contradicting evidence of a volume: quality relationship across all fields of medicine.…”
Section: Discussioncontrasting
confidence: 40%
“…Best practice guidelines have been developed to guide prostate cancer management and clinical indicators have been devised to measure how well prostate cancer care aligns with these guidelines [8][9][10][11]. Researchers in the US have led quality indicator development using a multi-step process involving literature review, focus groups with patients and family members, interviews with clinical experts and panel discussion from the fields of urology, radiation oncology, medical oncology and health services research [12].…”
Section: Introductionmentioning
confidence: 99%
“…299 With respect to provider cystectomy volumes, a systematic review of eight studies relating hospital cystectomy volumes to outcomes showed that each of the studies demonstrated improvement in at least one outcome with higher compared to lower volume. 304 Analyses of Canadian data have also consistently demonstrated that higher volume of cases correlates with better outcomes, including lower mortality risk. 290,291,305 Improving bladder cancer care…”
Section: Discussionmentioning
confidence: 99%
“…Over the last ten years, a large body of literature supporting the presence of a hospital volume-outcome relationship, including numerous systematic reviews, [18][19][20][21][22][23][24][25] has been developed. An early definitive systematic review on the subject was performed by Halm and colleagues and reported a significant association across a wide range of procedures and conditions.…”
Section: Discussionmentioning
confidence: 99%